Management of Iron Overload in Resource Poor Nations: A Systematic Review of Phlebotomy and Natural Chelators - Orish Ebere Orisakwe; Cecilia Nwadiuto Amadi; Chiara Frazzoli (Journal of Toxicology)
Iron is an essential element and the most abundant trace metal in the body involved in oxygen transport and oxygen sensing, electron transfer, energy metabolism, and DNA synthesis. Excess labile and unchelated iron can catalyze the formation of tissue-damaging radicals and induce oxidative stress. English abstracts were identified in PubMed and Google Scholar using multiple and various search terms based on defined inclusion and exclusion criteria. Full-length articles were selected for systematic review, and secondary and tertiary references were developed. Although bloodletting or phlebotomy remains the gold standard in the management of iron overload, this systematic review is an updated account of the pitfalls of phlebotomy and classical synthetic chelators with scientific justification for the use of natural iron chelators of dietary origin in resource-poor nations.